2010
DOI: 10.5004/dwt.2010.1110
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and specific ion effects on onion establishment in relation to disposal of desalting concentrates

Abstract: A B S T R AC TConcentrate from nanofi ltration (NF) is usually enriched with divalent ions, and low in proportions of monovalent ions. Therefore, its disposal to irrigation water may not be deleterious, especially for growing crops susceptible to specifi c effects of Na and/or Cl. This possibility was examined in a greenhouse by observing effects of four levels of salinity and ion composition of irrigation solutions on seedling emergence and growth of onions (sensitive to Cl ions) in loamy sand and silt loam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…1. This result is consistent with observations by Miyamoto et al (2010) whereby it was reported that salts can accumulate in the surfaces of poorly drained soils as a result of evaporation of saline water, which moves to the surface through capillary action. In the current study, salt accumulation in the surfaces of the silt loam soil was less dramatic.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1. This result is consistent with observations by Miyamoto et al (2010) whereby it was reported that salts can accumulate in the surfaces of poorly drained soils as a result of evaporation of saline water, which moves to the surface through capillary action. In the current study, salt accumulation in the surfaces of the silt loam soil was less dramatic.…”
Section: Resultssupporting
confidence: 93%
“…Overhead irrigation such as with a sprinkler may help seedling establishment resulting from lower soil salinity at top soil layer, which is evidenced in this experiment. Miyamoto et al (2010) reported that onion seedling emergence and growth were enhanced by overhead irrigation compared with subirrigation in loamy land. Therefore, irrigation with an overhead sprinkler, leaching salts, or increasing seeding density may be options to improve seedling establishment in salt-affected fields and with low-quality irrigation water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations